A Cost-Benefit Analysis of an Olympic Games - Darren McHugh (Queen's University, Department of Economics, 2006)
This paper attempts to estimate the net benefit to Canada of the Vancouver 2010 Winter Olympic Games. Two particular classes of problems in Olympic CBA are studied in detail. The first is the unique nature of project dependency in an Olympic Games, and this is surmounted by the classification of Olympic-related costs and benefits as "Event-related" or "Infrastructure-related", with rules for handing each in the context of a CBA for an Olympic Games. The second is the estimation of net benefit of three types of "Olympic Outputs", namely the Olympic Spectacle, the Olympic Halo (the feelings of pride engendered in the residents of the host city), and the tourism induced by an Olympic Games. One key result of the paper is that a correct accounting of induced Olympic tourism shows that the net benefit of this tourism is substantially less than its widely touted 'economic impact'. Although a detailed estimation of infrastructure costs and benefits is outside the scope of the paper, their contribution to the net benefit of the Games under the proposed project accounting rules is clearly negative. The net benefit of the Olympic Games is therefore also substantially negative when the estimates of Olympic benefits from this paper are combined with published estimates for event costs.
Keywords: D61; 330; Cost/Benefit Analysis; Olympics; Tourism